The Impact of Maternal and Household Characteristics on Childhood Impairments and Disabilities in Bangladesh - Khan, Naila Z; Ferdous, Shamim; Mahbub, Mustafa; Mobarak, Reaz; Parveen, Monowara; Mont, Daniel; Durkin, Maureen (Bangladesh Journal of Child Health, 2012)
Objective: To examine the risk factors associated with impairments and disabilities in children in Bangladesh. Methods: A two-stage methodology for identifying children with disabilities was employed in the Kishoreganj district of Bangladesh in 2001-2002. Ordered and generalized logit regressions were used to examine the correlation of childhood impairment and disability with a number of potential risk factors. Results: Children with consanguineous parents were 43.5% more likely to have an impairment; and poor children were 23.1% more likely. Maternal education reduced the chances of impairments developing into disabilities by 35%. Differences in risk factors existed between mild and severe disabilities. For example, boys were 66% more likely to have mild disabilities but not severe ones. Conclusions: Consanguinity and poverty are major factors associated with impairments, but maternal education might be an important tool towards limiting the probability of those impairments progressing to disabilities. Evidence also suggests that the causes of severe disabilities are significantly different from those causing mild disabilities. DOI: http://dx.doi.org/10.3329/bjch.v35i2.10353 Bangladesh J Child Health 2011; VOL 35 (2): 41-48